MULTICULTURALISM AND INTERCULTURAL EDUCATION: BETWEEN NEOINDIGENISM AND AUTONOMY (Andamios, Revista de Investigación Social, 2007)
This article analyzes government policies and the alternatives developed by a sector of the indigenous population in intercultural education, considered to be one of the fundamental aspects to understand multiculturalism. The author argues that current governmental initiatives in intercultural education, even if they consider the historic demands of indigenous people, they take said demands with a reduced vision of their implications. The alternative approaches to this governmental version of intercultural education, as this article shows, though they may tend toward the possibility of thinking about multiculturalism and interculturalism from different reference points, now face the challenge of updating their proposals to avoid getting coopted by neoindigenist discourses of governmental policies and institutions.
Keywords: Multiculturality; intercultural education; indigenism; indigenous autonomy; zapatismo